2010
DOI: 10.1152/ajpregu.00544.2009
|View full text |Cite
|
Sign up to set email alerts
|

Increased cyclooxygenase-2 expression and prostaglandin E2production in pressurized renal medullary interstitial cells

Abstract: Renal medullary interstitial cells (RMICs) are subjected to osmotic, inflammatory, and mechanical stress as a result of ureteral obstruction, which may influence the expression and activity of cyclooxygenase type 2 (COX-2). Inflammatory stress strongly induces COX-2 in RMICs. To explore the direct effect of mechanical stress on the expression and activity of COX-2, cultured RMICs were subjected to varying amounts of pressure over time using a novel pressure apparatus. COX-2 mRNA and protein were induced follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 35 publications
3
28
0
Order By: Relevance
“…We and others (6,15,24,27) have observed increased COX-2 expression in the renal inner medulla in response to ureteral obstruction. There is increasing evidence supporting a cytoprotective role of COX-2 in the renal medulla and increased COX-2 expression as a prerequisite for RMIC survival from hypertonic stress (13,14,33).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…We and others (6,15,24,27) have observed increased COX-2 expression in the renal inner medulla in response to ureteral obstruction. There is increasing evidence supporting a cytoprotective role of COX-2 in the renal medulla and increased COX-2 expression as a prerequisite for RMIC survival from hypertonic stress (13,14,33).…”
Section: Discussionmentioning
confidence: 53%
“…To explore the possible underlying mechanisms that link ROS and COX-2 in RMICs, the MAPK cascade was examined. MAPK pathways mediate the stimulatory effects of different extracellular stimuli on COX-2 expression in a stimulus-and cell type-specific manner (6,34), and studies have also demonstrated that oxidative and mechanical stress can stimulate MAPK pathways in various cell types (1, 3, 10, 31). Here, we studied different classes of MAPKs, including ERK1/2, p38, and JNK, and our data showed that the antioxidants DPI and ROT partly attenuated oxidative stress-induced phosphorylation of both ERK1/2 and p38 in RMICs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference may be explained by the fact that multiple biomechanical forces, other than CS, come into play in obstructive uropathy, such as hydrostatic pressure, which were not studied in the present investigation. In fact, several investigators have demonstrated that increases in intrarenal pressure stimulate COX-2 expression in interstitial cells, but not in the collecting duct, to induce PGE 2 expression (7,27). Therefore, because of the complexity of cell types and mechanical forces present in the hydronephrotic kidney, it is difficult to directly extrapolate our current findings to the hydronephrosis model.…”
Section: Cs Suppresses Pge 2 Releasementioning
confidence: 74%
“…This result is in good agreement with reported results that state that production of PGE 2 increases significantly in the kidney after UUO. 17,18,24,25 In addition, immunohistochemical analysis showed that main COX-2 immunoreactivities were localized to tubular epithelial cells after UUO, suggesting that PGE 2 produced by COX-2 in tubular epithelial cells exhibits some effects on neighboring cells, including tubular epithelial cells themselves and interstitial cells. In addition, we found that the expression level of EP 4 mRNA increases remarkably in WT kidneys after UUO.…”
Section: Discussionmentioning
confidence: 97%